Respon Imun Pada Penderita Cacar Monyet - Agnes Felicia Lubis (Oceana Biomedicina Journal, 2023)
Monkeypox is a viral infection caused by the orthopoxvirus. Following the global eradication of smallpox in 1977, monkeypox became the leading source of human monkeypox outbreaks, particularly in West and Central African nations where outbreaks typically occur in isolated locations. Monkeypox (monkeypox) displays clinical symptoms comparable to smallpox, such as flu-like symptoms, fever, lethargy, backache, headache, and rash. There is currently no treatment for monkeypox that infects people, however monkeypox may be diagnosed by biomolecular investigation using PCR-RFLP.